2019
DOI: 10.1590/1980-5373-mr-2018-0847
|View full text |Cite
|
Sign up to set email alerts
|

Fe3O4@C core-shell nanoparticles as adsorbent of ionic zinc: evaluating of the adsorptive capacity

Abstract: Zinc is an important chemical element in many metabolic mechanisms at low concentrations, but can be toxic when administrated in doses higher than 500 µg•g-1 or 3 mg•L-1. This metal has been detected in many aquatic environments due to several industry activities and swine manure effluents. Thus, the contaminant removal of water and wastewater has been a major challenge. Many processes are applied and evaluated in an attempt to removal zinc found in environment, such as adsorption. In the present study Fe 3 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
1
5
0
1
Order By: Relevance
“…The lower toxicity of MgO‐NPs in comparison to MgO and Mg (NO 3 ) 2 ·6H 2 O found in the present study may be related to the tendency that NPs have in forming clusters due to the strong surface energy of nanoparticles (Costa et al, 2019; Pan & Xing, 2012), observed in the characterization of MgO‐NPs in our study, where they show irregular clusters with diameters from 300 to 500 nm. Ghobadian et al (2015), in their study with MgO‐NPs in zebrafish, concluded that NPs with size of 20 nm have higher toxicity when compared to aggregated NPs and that MgO‐NPs are less toxic when compared to non‐nano MgO, due to this characteristic of association.…”
Section: Discussionsupporting
confidence: 47%
“…The lower toxicity of MgO‐NPs in comparison to MgO and Mg (NO 3 ) 2 ·6H 2 O found in the present study may be related to the tendency that NPs have in forming clusters due to the strong surface energy of nanoparticles (Costa et al, 2019; Pan & Xing, 2012), observed in the characterization of MgO‐NPs in our study, where they show irregular clusters with diameters from 300 to 500 nm. Ghobadian et al (2015), in their study with MgO‐NPs in zebrafish, concluded that NPs with size of 20 nm have higher toxicity when compared to aggregated NPs and that MgO‐NPs are less toxic when compared to non‐nano MgO, due to this characteristic of association.…”
Section: Discussionsupporting
confidence: 47%
“…The majority of Fe 3 O 4 @C composites applications are in electronics (used as supercapacitors [177], anode materials in lithium-ion batteries [178], absorbents [177]). These materials can be obtained by in situ or post-synthesis functionalization, using the hydrothermal approach [179][180][181].…”
Section: Carbon-based Functionalization Of Magnetite Nanoparticlesmentioning
confidence: 99%
“…In fact, the surface modication over SCMBNPs by organic molecule and metals can be adjudged from its appearances. 28,29 The elemental mapping obviously exhibit that metals dispersed uniformly on the surface of naked SCMBNPs as shown in Fig. 4 https:// www.nature.com/articles/s41598-018-19551-3 -Fig.…”
Section: Structural Characterization Of Nanodendrimersmentioning
confidence: 99%